South African tabloid newspapers’ representation of black celebrities: A social constructionism perspective - Matsebatlela, Emmanuel Mogoboya (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Journalism))--University of Stellenbosch, 2009.